Mechanical implications of the mandibular coronoid process morphology in Neandertals. Issue 2 (15th February 2018) - Marom, Assaf; Rak, Yoel
Abstract: Objectives: Among the diagnostic features of the Neandertal mandible are the broad base of the coronoid process and its straight posterior margin. The adaptive value of these (and other) anatomical features has been linked to the Neandertal's need to cope with a large gape. The present study aims to test this hypothesis with regard to the morphology of the coronoid process. Materials and Methods: This admittedly simple, intuitive hypothesis was tested here via a comparative finite‐element study of the primitive versus modified state of the coronoid process, using two‐dimensional models of the mandible. Results: Our simulations demonstrate that a large gape has an unfavorable effect on the primitive state of the coronoid process: the diagonal, almost horizontal, component of the temporalis muscle resultant (relative to the long axis of the coronoid process) bends the process in the sagittal plane. Furthermore, we show that the modification of the coronoid process morphology alone reduces the process' bending in a wide gape increasing the compression to tension ratio. Discussion: These results provide indirect evidence in support of the hypothesis that the modification of the coronoid process in Neandertals is necessary for enabling their mandible to cope with a large gape.